PENGARUH FINANCIAL LEVERAGE, DIVIDEND PAYOUT RATIO, DAN PENERAPAN CORPORATE GOVERNANCE TERHADAP PRAKTIK PERATAAN LABA - Widhyawan, I Made Indra; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2016)
Income smoothing is the management effort to reduce fluctuations in reported earnings to achieve the desired level of profit. Income smoothing can improve the relationship between management and external parties for the performance of the company becomes visible stable but income smoothing can cause the credibility of the financial statements to be reduced. This study aims to examine the factors that affect income smoothing. The study population was participating companies CGPI (Corporate Governance Perception Index) are listed on the Indonesia Stock Exchange from 2010-2013. Sampling method used was non-probability sampling. The Selected samples of 10 companies through pre-defined criteria. Eckel index used to identify companies that do and do not do income smoothing. Hypothesis testing using is multiplelinear regression analysis techniques . Based on the results of tests carried out showed that the variables financial leverage positive effect on income smoothing and corporate governance negatively affect income smoothing , while the dividend payout ratio variable has no effect on income smoothing.
Keywords: Income smoothing, financial leverage, dividend payout ratio, and corporate governance.